The "Sudden" Transition to the Free Floating Exchange Rate Regime in Russia in 2014 - V. Gilenko, Evgenii (Journal of Reviews on Global Economics, 2017)
The events of the fall of 2014 in the Russian currency market forced Bank of Russia to change the exchange rate regime in the national economy. In this study we show that in 2014 the regulator was trying to protect ruble (the Russian national currency) against a massive speculative attack, actively spending its international reserves, but the interventions proved quite ineffective. Moreover, the peculiarity of the structure of these reserves dictated a very limited range of maneuver for the central bank, forcing it to switch to the free floating exchange rate regime in the first half of November, 2014 - an important event, which, actually, could have been predicted by the lay experts on the basis of publically available information and application of simple econometric models. Noteworthy to say that, although not expectedly to the lay population, this switch of the exchange rate regime was done by Bank of Russia quite timely.